Fedorenko S. V. Intercultural aspect of scientific literature translation - Fedorenko S. V. (Philological Treatises, 2020)
This paper deals with scientific translation as the special means of multilingual information exchange and intercultural activity. The problems of producing a convincing target text, which relate to the use of terms, are generalized.